Performance of TCM systems with outer codes overfrequency-selective slowly-fading channels - Al-Semari, S.A. (1993)
This paper proposes the use of an inner trellis code in a concatenated system for communication over frequency-selective slowly-fading channels. Performance is evaluated for the proposed system and the results indicate the superiority over conventional systems